ANALISIS TINGKAT KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (STUDI KASUS DI KANTOR BADAN PENDAPATAN DAERAH KABUPATEN TAKALAR) - Abdul Muthalib; Sitti Hajerah Hasyim; Nur Afiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the factors influencing the compliance of Rural and Urban Land and Building Tax (PBB-P2) taxpayers and to evaluate its contribution to Local Own-Source Revenue (PAD) in Takalar Regency. A descriptive qualitative approach was employed, supported by quantitative data on tax revenue targets and realization for 2020–2024. Data were collected through interviews with four informants (three BAPENDA staff and one taxpayer), and documentation, then analyzed using the interactive qualitative model of Miles and Huberman. The findings show that taxpayer compliance is influenced by four main factors: delays in the distribution of Tax Due Notification Letters (SPPT), limited taxpayer understanding of taxation, cultural barriers and limited access to information, and taxpayer behavior that tends to wait for reminders before paying. In addition, the contribution of PBB-P2 to Takalar's PAD during 2020–2024 remained very low, ranging from 2.37% to 2.94%, and the nominal increase in tax revenue realization was not followed by a proportional increase in its contribution to PAD. These findings underline the need to strengthen tax services, optimize digital technology, and raise public awareness so that the contribution of PBB-P2 to regional fiscal independence can be improved.